2022
DOI: 10.1177/17579759211065489
|View full text |Cite
|
Sign up to set email alerts
|

Is social media, as a main source of information on COVID-19, associated with perceived effectiveness of face mask use? Findings from six sub-Saharan African countries

Abstract: Background: The use of face masks as a public health approach to limit the spread of coronavirus disease 2019 (COVID-19) has been the subject of debate. One major concern has been the spread of misinformation via social media channels about the implications of the use of face masks. We assessed the association between social media as the main COVID-19 information source and perceived effectiveness of face mask use. Methods: In this survey in six sub-Saharan African countries (Botswana, Kenya, Malawi, Nigeria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Higher rates of good attitudes and perceptions were also reported in Western Uganda [18] and Egypt [21], but a lower rate of perceived benefits of preventive measures was reported in Addis Ababa, Ethiopia [22]. Similar findings of good perception were also reported in the Greater Kampala Metropolitan area of Uganda and in other 6 countries (Botswana, Kenya, Malawi, Nigeria, Zambia, and Zimbabwe), where a great majority of the residents believed that face masks were effective against COVID-19 spread and infection [23,24]. However, most individuals in Nigeria believed that COVID-19 was more of a hoax than a reality, and in several countries, preventive measures such as social distancing and face masking were perceived as imported policies that negatively affected their compliance with preventive measures to curb the spread of the disease [25,26].…”
Section: Knowledge and Perception Of Ppms And Associated Factorssupporting
confidence: 63%
See 1 more Smart Citation
“…Higher rates of good attitudes and perceptions were also reported in Western Uganda [18] and Egypt [21], but a lower rate of perceived benefits of preventive measures was reported in Addis Ababa, Ethiopia [22]. Similar findings of good perception were also reported in the Greater Kampala Metropolitan area of Uganda and in other 6 countries (Botswana, Kenya, Malawi, Nigeria, Zambia, and Zimbabwe), where a great majority of the residents believed that face masks were effective against COVID-19 spread and infection [23,24]. However, most individuals in Nigeria believed that COVID-19 was more of a hoax than a reality, and in several countries, preventive measures such as social distancing and face masking were perceived as imported policies that negatively affected their compliance with preventive measures to curb the spread of the disease [25,26].…”
Section: Knowledge and Perception Of Ppms And Associated Factorssupporting
confidence: 63%
“…As possible predictors, educational level, age, income, residence, frequency of PPE practice, PPE attitude, social media exposure, and perceived threat were associated with knowledge and perception of PPMs among the general population, HCWs, and other groups (taxi drivers and government employees) [18,23,24,42,43,68,70,71]. Moreover, practice location was notably significantly associated among HCWs [43] (Table 3).…”
mentioning
confidence: 97%
“…Surprisingly, however, approximately three-quarters of the survey fillers noted that they get information directly from governmental press conferences. This result, when compared with the rest of the world, is unique (20,21). The Qatari government has proved to be a leader in information campaigns regarding this pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, there are no clear guidelines directing the safe use of masks among individuals with emotional disorders. The survey found that more than one-half of respondents used social media as the main source of information on COVID-19 48 and information searches on social media were positively correlated with mask use. Findings of the present study can be used to analyze mask use in anxious patients, improve the public’s COVID-19-related health beliefs, and adjust mask-wearing recommendations.…”
Section: Discussionmentioning
confidence: 99%